HOME GOVERNMENT: DOMESTICITY AND ITS PROBLEMATIZATION IN SOCIAL QUESTION DEBATE IN ARGENTINA (1890-1940) - Aguilar, Paula Lucía (2013)
This article proposes, from a genealogical perspective, an overview of the configuration of domesticity as it emerges in the debates about the social question. It examines the way in which home arises in two areas of great debate problematizations: the opposition of home and workspace and the “housing question” in order to give account for the main features of the historical formation of domesticity.